The POCUS Lesson of Professor Tulp - James S. Newman (CINQUILL Medical Publishers Inc., 2021)
An homage to Rembrandt's "The Anatomy Lesson of Dr. Nicolaes Tulp" for the modern physician (Acrylic on canvas).